The Effect of Reminiscence Therapy Using Video on the Cognitive Function of the Elderly at Panti Pelayanan Sosial Lanjut Usia (PPSLU) Sudagaran - Erismanto Erismanto; Rakhmat Susilo (UM Purwokerto Press, 2021)
By the increase in the quantity of the elderly, the percentage of health problems will also rise. The decline in cognitive function is an important problem to overcome for the welfare of the elderly. Cognitive function can be maintained with non-pharmacological therapy, namely reminiscence therapy. Reminiscence therapy can be given through various media, one of which is video. Video has advantages in terms of providing good visualization to facilitate the process of recognizing, recalling, and connecting facts and concepts. To determine the effect of reminiscence therapy through video media on the cognitive function of the elderly at Panti Pelayanan Sosial Lanjut Usia (PPSLU) Sudagaran. This was quantitative research. The pre-experimental method was employed with Pre Post Test One Group design. The sample was 45 respondents, obtained by using the probability sampling technique with purposive sampling. The results showed that the average age of the respondents was 72.07 years old. They were 28 (62.2%) females and 17 (37.8%) males. Before the intervention, the average value of the cognitive function of the elderly was 15,563,526. After the therapeutic intervention, there was an improvement with an average value of 18,242,673. The results of the paired sample t-test showed a significant value of p = 0.001 (p (0.05) with an effect size value of r = 0.87. There was an effect of reminiscence therapy through video media on the cognitive function of the elderly at Panti Pelayanan Sosial Lanjut Usia (PPSLU) Sudagaran.